2004
DOI: 10.1080/15325020490255322
|View full text |Cite
|
Sign up to set email alerts
|

Bereavement by Traumatic Means: The Complex Synergy of Trauma and Grief

Abstract: When people lose intimates unexpectedly, in particular from malicious acts of violence, they are at risk for chronic grief reactions. The phenomenology, clinical symptoms, clinical needs, and risk factors associated with loss by traumatic means and the combined influences of loss and trauma exposure are yet to be systematically studied. We review the complex interplay between trauma and loss by traumatic means. The distinctions between normal and traumatic loss, and complicated and traumatic grief, are contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(83 citation statements)
references
References 43 publications
3
79
0
1
Order By: Relevance
“…Second, this study did not include a specific measure of complicated grief. It is likely that in addition to the DSM-IV disorders studied here, some patients developed specific grief reactions associated with post-trauma psychopathology (Neria & Litz, 2004, Neria et al, 2007. Third, because the study was undertaken in an urban general medical practice serving a low-income population, the results may not generalize to primary care settings with different populations (Bruce, Takeuchi, & Leaf, 1991).…”
Section: Discussionmentioning
confidence: 78%
“…Second, this study did not include a specific measure of complicated grief. It is likely that in addition to the DSM-IV disorders studied here, some patients developed specific grief reactions associated with post-trauma psychopathology (Neria & Litz, 2004, Neria et al, 2007. Third, because the study was undertaken in an urban general medical practice serving a low-income population, the results may not generalize to primary care settings with different populations (Bruce, Takeuchi, & Leaf, 1991).…”
Section: Discussionmentioning
confidence: 78%
“…Both clinical experience and research have identified problems related to the interplay between trauma and grief, and if a person is present and witness to a death, or the traumatic circumstances surrounding the death easily gives rise to inner images of what happened, it may be very difficult to think of memories of that person without the «traumatic» circumstances invading their thoughts (Neria & Litz, 2004). Bereavement after the unexpected loss of a loved one is associated with elevated risk for an onset of PTSD, panic disorder, depressive episodes, and multiple psychiatric disorders like mood and anxiety disorders (Keyes et al, 2014).…”
Section: Additional Stressors Related To the Lossmentioning
confidence: 99%
“…Loss of this kind can be conceptualized as a trauma stressor that can lead to traumatic stress. Therefore, there is a great deal of intersection between trauma loss and trauma stress, both in event dimensions and psychological outcome (Neria & Litz, 2004). In trauma loss, a person is forcefully separated from his or her family member or close friends by death or other reasons.…”
Section: Trauma and Lossmentioning
confidence: 99%